(untitled) (Bangladesh Journal of Medical Education, 2021)
This descriptive type of cross-sectional study was driven to explore the teachers’ view about feminization of medical education in Bangladesh. This study was carried out in 4 government and 4 non-government medical colleges of Bangladesh during the period of July 2019 to June 2020. From all four phases, total 104 teachers were respondents of this study to seek information regarding the factors affecting and effects of feminization of medical education in Bangladesh with a pretested self-administered questionnaire. The study revealed that high social respect, high marriage value, parental pressure, financial security are the factors for feminization of medical education in Bangladesh. Other factor that may influence female students to get admitted in the MBBS course is female students are more studious. There are limited better alternate profession for female students. This study also revealed that empathetic to patients are more satisfied with female doctors, they like some specific subspecialty as their career choice and feminization do not hamper quality of health care. 46 (44.2%) teachers were disagreed that female doctors like to work in rural area. and 49 (47.1%) teachers were disagreed that female doctors are efficient in medical emergency management during disaster. Study recommended establishment of female friendly working environment at all levels of the hospital. Study also recommended further long term and wider scale study with more participants to observe the impact of feminization of medical education on health care delivery system in Bangladesh Bangladesh Journal of Medical Education Vol.12(2) July 2021: 4-9